Fiscal policy and growth forecasts in the EU: Are official forecasters still misestimating fiscal multipliers? - David Cronin; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2020)
Blanchard and Leigh (2013, 2014) find fiscal multipliers to be underestimated in the EU in the deep recession of the early 2010s. Using two 2013-2018 datasets for 26 EU member states, assembled from Stability and Convergence Programmes and the European Commission's Spring Forecasts, we show that multiplier estimates in the EU have been overestimated in the post-crisis period. Forecasters then are still not capturing accurately the impact that fiscal policy has on output growth rates and are misestimating in a manner opposite to that reported by Blanchard and Leigh. This result is pertinent at a time when fiscal stimulus is occurring in many member states in response to the adverse economic effects of Covid-19.
Keywords: C23; E62; H68; 330; Fiscal policy; Multipliers; Forecast errors